Self-confidence, motivation, and concentration as predictors of perceived futsal knowledge in physical education students - Imanuddin Siregar; Alwi Fahruzy Nasution (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Conceptual understanding in futsal learning remains a challenge for physical education students, who often prioritize practical performance over theoretical engagement. This study aims to examine the influence of self-confidence, motivation, and concentration on undergraduate students' perceived knowledge of futsal in the Physical Education, Health, and Recreation (PJKR) program at Universitas Pembinaan Masyarakat Indonesia. A quantitative correlational design with a cross-sectional approach was employed. Data were collected from 115 students using Likert-scale questionnaires measuring self-confidence, motivation, concentration, and perceived futsal knowledge. The data were analyzed using multiple regression after the assumptions for regression were met. The results showed that self-confidence (t = 5.606, p < .001), motivation (t = 2.333, p = .021), and concentration (t = 2.187, p = .031) each had a positive and significant effect on perceived futsal knowledge. Collectively, these variables significantly predicted perceived futsal knowledge (F = 16.552, p < .001), accounting for 30.9% of the variance, indicating a moderate explanatory power. These findings suggest that psychological factors contribute meaningfully to students’ perceived understanding in futsal learning, although a substantial proportion of variance remains influenced by other factors. This study extends sport education research by highlighting the role of psychological variables in shaping perceived conceptual understanding. It expands the field's scope by examining psychological predictors of perceived conceptual knowledge in futsal learning, emphasizing the importance of addressing psychological factors and integrating psychological support into instructional design in physical education to enhance students' conceptual engagement.